BEYOND PROFIT DALAM MENGGAGAS MODEL PERBANKAN SYARIAH YANG HUMANIS DAN INKLUSIF - Maulana, Fadhil (Finance : Journal of Accounting and Finance, 2025)
Sharia banking has often been understood as merely an interest-free financial alternative, when in fact its essence is much deeper and broader. This article proposes a model of sharia banking that is not only profit-oriented but also promotes humanistic values and social inclusiveness. Through a maqashid-based approach, Islamic finance should aim to create economic justice, empower communities, and address structural inequalities. By integrating ethical principles, civilized digitalization, and expanding access for vulnerable groups, Islamic banks can play a transformative role in social development. This article emphasizes that the success of future Islamic banking is not only measured by profitability, but by how far it can dignify humanity and bridge those who are economically left behind. Thus, the “beyond profit” initiative is an important step toward banking that is not only Islamic in form, but also in spirit.